Es gibt weiterhin ökonomische Argumente für einen öffentlichen Rundfunk - Rafael Aigner; Anselm Mattes; Ferdinand Pavel (Wirtschaftsdienst, 2017)
Die Finanzierung des öffentlich-rechtlichen Rundfunks in Deutschland steht in der Kritik. Vielfach wird bezweifelt, dass eine öffentliche Finanzierung von Rundfunkanstalten aus ordnungspolitischer Perspektive noch gerechtfertigt werden kann. Die Autoren argumentieren, dass es trotz technologischer Veränderungen weiterhin ökonomisch fundierte Gründe für eine öffentliche Finanzierung von Rundfunkinhalten gibt. Grundlage der Argumentation sind die positiven externen Effekte des Rundfunks. – – Recent economic literature criticises the size and mandate of public broadcasting in Germany. Technological progress has changed the methods of producing and distributing broadcasting content. Traditional broadcasting and print media have converged in a digital environment. Some of the classical arguments for publicly funded broadcasting have become invalid. This article argues that the converging media markets are nonetheless characterised by ongoing market failures, mostly because of positive external effects created by public value content. Markets will underprovide such content, which is why they should be publicly funded. We discuss the scope and form of public broadcasting and conclude that there are still economic reasons for dedicated public service broadcasters to exist.
Keywords: H4; L82; D62; 330